Penamaan Desa Di Kecamatan Rupat Utara Kabupaten Bengkalias (Kajian Antropolinguistik) - Ahda Maleta Zahra; Hesty Elfianora; Nurvilla Nurvilla; Rina Sukmawati; Muhammad Mukhlis (UIR Press, 2022)
Humans who live in a certain area have a clear purpose and purpose. Just as humans inhabit an area on earth, humans will give names to all elements of geography, such as the names of rivers, hills, mountains, valleys, islands, bays, seas, straits, and so on that are in their territory. Naming is a process of symbolizing a concept to refer to a referent. Giving a name to each area is not only for designation but to make it easier for someone to recognize the identity of the area. North Rupat District is one of the sub-districts in Bengkalis Regency. Not many people know the shape and meaning of the origin or story of naming villages in North Rupat District. Naming and naming a place and region comes from the names of people, plants, history and so on. In this study there are several problems how the cultural values contained in the naming of villages in North Rupat District. This study aims to identify, analyze, and interpret the form of village naming in North Rupat District, to identify, analyze, and interpret the meaning of village naming in North Rupat District, and to know the cultural values contained in village naming in North Rupat District. This study uses an anthropolinguistic study that connects the study of language and culture. This research uses descriptive qualitative method. The method used in data collection is a research method. The interview technique carried out by the researcher used the note- taking technique. The cultural values contained in the Village Naming, Rupat Utara District, Bengkalis Regency are the value of peace, the value of positive thinking culture, and the cultural value of preservation and creativity.